Creative Construction Conference 2018 - Proceedings 2018
DOI: 10.3311/ccc2018-132
|View full text |Cite
|
Sign up to set email alerts
|

Developing an interoperability framework for building information models and facilities management systems

Abstract: Despite the fact that the value of extending Building Information Modeling (BIM) implementation through the operations and maintenance phase is simply to reduce the operations and maintenance costs associated with inadequate interoperability, facilities management information flow is neither automated nor seamless. Facility managers do not normally use BIM models data, since they claim that BIM models either do not include their information requirements, or contain a huge amount of superfluous data which makes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…Several contributions have been added, investigating the value and challenges of BIM, not only in the facilities management context, but also with focus on BM and existing buildings. Some works have accomplished this, both through literature reviews (Volk et al , 2014; Ilter and Ergen, 2015; Aziz et al , 2016b; Pärn et al , 2016; Kelly et al , 2013) and through various other studies (Ahn and Cha, 2014; Barbosa et al , 2016; Sampaio et al , 2016; Alwan, 2016; Cheng et al , 2016; Bortolini et al , 2016; Cecconi et al , 2018; Carbonari et al , 2018; Matarneh et al , 2018; Mirarchi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several contributions have been added, investigating the value and challenges of BIM, not only in the facilities management context, but also with focus on BM and existing buildings. Some works have accomplished this, both through literature reviews (Volk et al , 2014; Ilter and Ergen, 2015; Aziz et al , 2016b; Pärn et al , 2016; Kelly et al , 2013) and through various other studies (Ahn and Cha, 2014; Barbosa et al , 2016; Sampaio et al , 2016; Alwan, 2016; Cheng et al , 2016; Bortolini et al , 2016; Cecconi et al , 2018; Carbonari et al , 2018; Matarneh et al , 2018; Mirarchi et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature reviewed by Kelly et al (2013) on BIM for facility management showed that its value adding potential comes from the improvement to current manual processing of information handover as well as to the accuracy of facility management data. Matarneh et al (2018) also asserts that although there are commercially available technologies for transferring data between BIM models and facilities management systems, the process may not be straightforward or cost effective. The lack of interoperability between software systems and a limited integrated view of multiple domains for decision support, are some of the limitations to explain why the potential of BIM in the O&M phases has not been fully utilised (Cheng et al , 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…BIM objects can be the container for exchanging information, and open format files can guarantee technical interoperability and software independency, as Hjelseth has suggested [9]. However, in current practice, information flow is neither automated nor seamless, as the theory illustrates [10] and it has been estimated that, in 2002, inadequate interoperability caused an annual cost of $15.8 billion in the U.S. capital facilities industry [11].…”
Section: State Of the Artmentioning
confidence: 99%
“…The inherent power of BIM for FM is mainly associated with streamlining information flow between the project stakeholders during the facility lifecycle and facilitating information handover to FM teams (Matarneha et al, 2018;Reza Hosseini et al, 2018). Yet information flow among project stakeholders is neither automated nor seamless.…”
Section: Research Background and Related Studiesmentioning
confidence: 99%